2020
DOI: 10.1590/fst.31719
|View full text |Cite
|
Sign up to set email alerts
|

Improving composition and microbiological characteristics of milk kefir using colostrum

Abstract: Kefir characteristics are influenced by raw materials. Fresh milk and colostrum have different characteristics. In this research, colostrum was used as additional material in kefir production which could affect the chemical, microbiological, and antimicrobial properties of final the product. This study was aimed to investigate the chemical and microbiology properties of kefir prepared from milk, colostrum and milk-colostrum mixes. Kefir was prepared by adding kefir grains to 100% fresh milk, milk-colostrum mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
5
4
Order By: Relevance
“…We observed the decrease on days 7 and 14 of storage that could be associated with the growing fungi. Compared to previous findings, the mean of total solids in this study was 17.39% higher than 12.09%, 12.37%, and 14.59 from goat milk kefir (Cais-Sokolińska et al, 2015;Satir & Guzel-Seydim, 2016;Setyawardani et al, 2014), 9.49% from ginger-added cow milk kefir (Wulansari & Rahayu, 2019) and 14.84% from cow colostrum kefir (Setyawardani et al, 2020).…”
Section: Chemical Characteristicscontrasting
confidence: 88%
See 1 more Smart Citation
“…We observed the decrease on days 7 and 14 of storage that could be associated with the growing fungi. Compared to previous findings, the mean of total solids in this study was 17.39% higher than 12.09%, 12.37%, and 14.59 from goat milk kefir (Cais-Sokolińska et al, 2015;Satir & Guzel-Seydim, 2016;Setyawardani et al, 2014), 9.49% from ginger-added cow milk kefir (Wulansari & Rahayu, 2019) and 14.84% from cow colostrum kefir (Setyawardani et al, 2020).…”
Section: Chemical Characteristicscontrasting
confidence: 88%
“…The increased acidity can be due to the acidic composition of Moringa oleifera leaf powder that subsequently increased the kefir acidity (Mbikay, 2012). The acidity level in this study remains lower than 1.31-1.66% reported by Setyawardani et al (2020).…”
Section: Chemical Characteristicscontrasting
confidence: 52%
“…However, we did not observe any linear increase in the fat content of GY increasing colostrum levels in the formulations. In the study of Setyawardani et al (2020), no significant differences were observed in fat content among kefir samples produced with increasing bovine colostrum percentages, which were even higher than those used in our study (0, 20, 40, 60, 80 and 100% colostrum).…”
Section: Chemical Compositioncontrasting
confidence: 78%
“…Microbiology analysis of the product including total microbe of the product refers to the method of Setyawardani et al (2020) using plate count agar as media, total yeast refers to the method of Al-Baarri et al (2020) using potato dextrose agar as media and total lactic acid bacteria refers to the method of Rahayu and Andriani (2018) using Mann de rogosa agar as media.…”
Section: Microbiology Analysismentioning
confidence: 99%